MANEJEMEN LAYANAN PERPUSTAKAAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN KEBUPATEN KARANGANYAR - Winarno; Yunita Maysyaroh; Sawiji, Hery (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
The objectives of this study were to 1) describe library service management at the Karanganyar Regency Archives and Library Service, 2) identify the obstacles; and 3) identify the efforts made to overcome the obstacles that occurred. This research approach is descriptive qualitative with a case study type. Data sources come from informants/resources, places and events, and documents and archives. The sampling techniques used were purposive sampling and snowball sampling. The data collection techniques used were interviews, observation, and document and archive analysis. Data validity uses data source triangulation and method triangulation techniques. Data analysis used in this research is an interactive analysis technique. The results of this study are as follows: Library service management at the Karanganyar Regency Archives and Library Service is carried out based on 4 management functions, namely planning, organizing, implementing/moving, and supervising. The obstacles faced in service management at the Karanganyar Regency Archives and Library Service are limited collections, lack of facilities and infrastructure, lack of competent librarians, and low interest in reading from library service users. The solution to overcome the obstacles that occur in library service management at the Karanganyar Regency Archives and Library Service is to carry out procurement of library materials, procurement of facilities and infrastructure, guidance and coaching for librarians, and promotion of library services to the community.